Objectively measured physical activity of hospital shift workers - Loef, Bette; van der Beek, Allard J.; Holtermann, Andreas; Hulsegge, Gerben; van Baarle, Debbie; Proper, Karin I. (Scandinavian Journal of Work, Environment & Health, 2018)
' ' OBJECTIVES ': 'Shift work may alter workers’ leisure-time and occupational physical activity (PA) levels, which might be one of the potential underlying mechanisms of the negative health effects of shift work. Therefore, we compared objectively measured PA levels between hospital shift and non-shift workers. ' ' METHODS ': 'Data were used from Klokwerk+, a cohort study examining the health effects of shift work among healthcare workers employed in hospitals. In total, 401 shift workers and 78 non-shift workers were included, all of whom wore Actigraph GT3X accelerometers for up to seven days. Time spent sedentary, standing, walking, running, stairclimbing, and cycling during leisure time and at work was estimated using Acti4 software. Linear regression was used to compare proportions of time spent in these activities between hospital shift and non-shift workers. ' ' RESULTS ': 'Average accelerometer wear-time was 105.9 [standard deviation (SD) 14.0] waking hours over an average of 6.9 (SD 0.6) days. No differences between hospital shift and non-shift workers were found in leisure-time PA (P>0.05). At work, shift workers were less sedentary [B=-10.6% (95% CI -14.3– -6.8)] and spent larger proportions of time standing [B=9.5% (95% CI 6.4–12.6)] and walking [B=1.2% (95% CI 0.1–2.2)] than non-shift workers. However, these differences in occupational PA became smaller when the number of night shifts during accelerometer wear-time increased. ' ' CONCLUSIONS ': 'Leisure-time PA levels of hospital shift workers were similar to those of non-shift workers, but shift workers were less sedentary and more physically active (ie, standing/walking) at work. Future research to the role of occupational activities in the health effects of shift work is recommended.
Keywords: accelerometry; healthcare worker; hospital; hospital worker; leisure-time physical activity; night shift work; night work; objective measure; occupational health; occupational physical activity; physical activity; shift work; shift worker; workhour